Modifikasi Sekop Mixer Bed Dryer Automixing Untuk Memaksimalkan Pembalikan Gabah - Bambang Edi Sutejo; Yus Witdarko; Ni Luh Sri Suryaningsih (Universitas Musamus, Merauke, Papua, 2018)
The research was aim to modify the shovel of the microcomputer or the inverting component of bed dyer automixing and to test the bed dyer automixing machine which has been modified by its reversing component. The research was conducted at BBI Padi Kurik of Merauke Regency in July 2017. The main parameter in this research is found on microcop spade. This modification aims to refine the muzzle shovel where in the uneven grain reversal, so the level of drought is not evenly distributed. The data analysis was done by comparing the decrease of water content of grain tested with grain moisture meter, so that the comparison between bad dryer automixing before and after modified. The results of the analysis on the tool test showed significant differences a mean and significant difference, both KA and uniform dryness level. The average decrease in KA with unmodified tools during 8 hours of testing was 5.1%, whereas with the modified tool 6.53%.